THE ROLE OF SOCIAL NORMS IN TAX COMPLIANCE BEHAVIOUR OF SMES IN EMERGING ECONOMIES LIKE UGANDA. - Festo Nyende Tusubira, (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
Taxpayers have different motivations for paying taxes. How successfully taxpayers comply with the tax system will depend on the social standing of the taxpayers and the ability of the tax authority to impose the legal requirements for such a system. We have had minimal corporate tax revenue contributions to the overall tax revenue in Uganda, especially from small and medium corporations over the past decade and relatively little attention has been directed towards understanding what the challenge could be. Could corporate tax compliance behaviour be determined by the power dimensions or social psychological stance, and in which magnitude? Evidence has cast doubt on the ability of power dimensions to effectively influence tax compliance behaviour, suggesting that social norms may be an influential tool in determining tax compliance behaviour. Combining descriptive and analytical research design and utilising a structural equation model, the study helps to provide answers to these questions using social norms theory and the slippery slope framework. Descriptive norms generally have significant direct effects on tax compliance behaviour.